FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN MOTIVASI KERJA PADA PERAWAT RUMAH SAKIT JIWA (Studi Pada Bangsal Kelas III RSJD Dr.Amino Gondohutomo Provinsi Jawa Tengah) - Intan Dwi Cahyani; Ida Wahyuni; Bina Kurniawan (Jurnal Kesehatan Masyarakat (Undip), 2016)
Motivation is the things that cause, distribute, and support of human behavior in order to work diligently and enthusiastically to achieve optimal results and high productivity. This research aims to know the factors related with motivation to work in a psychiatric hospital’s nurse. Type of this research is explanatory research using cross sectional approach. Total population 91 people with a cross-sectional sample calculation formula so that the resulting number of samples 47 and are determined using purposive random sampling technique. The survey results revealed that as many as 57.4% of respondents have moderate motivation and 23.4% had low motivation. Statistical analysis showed that there are correlation between age (p = 0.007), employment period (p = 0.0001), work achievement (p = 0.0001), recognition (0.0001), the potential development of the individual (p = 0.001), perception of salary (0.0001), working conditions (p = 0.002), policy and administration (p = 0.045), personal relationships (p = 0.006), supervision (p = 0.022) with the motivation to work. There was no correlation between status of marriage (p = 0.526), work it self (p = 0.210), responsibility (0.773) with work motivation. Advised the management of mental hospitals always provide motivation for nurses. Suggestions for nurses should always increase the motivation, improve cooperation both with colleagues and superiors so as to improve working relationships and good working conditions.